Absorption study of bis phenol a using molecular imprinted membrane - Siti Fairun Annisha, Hassan (2013)
Endocrine disruptors component (EDCs) are environmental chemicals that affect the function of the endocrine system, the system relating the glands and hormones of the body. In this study, Bisphenol A (BPA) has selected for evaluation because it has acknowledged significant consideration in recent years due to widespread human exposures and concern for reproductive and developmental effects toward health. There is some evidence that endocrine disruptors may not only impact the individual directly exposed, but also future generations. So, the removal of BPA must be efficient to protect our new generation and environment. In this study, Molecular Imprinted polymer (MIP) has been chosen because of their advantages such as MIPs possess excellent selective adsorption for templates due to the stereoscopic shape of specific cavity and interactions. Thus, this research is aims to practice the removal of BPA from aqueous solution by adsorption using an effective, reusable and low cost method like molecular Imprinted membrane that have highly selective factor. The MIP was synthesis by using bulk polymerization process and imprinted membrane were prepared by using phase inversion method. The adsorption kinetics was studied by stirring BPA-MIP, NIM and BPA-MIM in BPA aqueous solution for different times. The adsorption isotherms were studied by stirring BPA-MIP, NIM and BPA-MIM in BPA solution at different concentration. The maximum adsorption capacity of BPA ions for the NIM, BPA-MIM, and BPA-MIP was 0.1268 mmol/g, 0.1328 mmol/g, 0.1149 mmol/g respectively. In this study, it can be conclude that the MIP in membrane can absorb the BPA more than BPA-MIP powder, and membrane alone.